Development of local wisdom-based Subject-Specific Pedagogy (SSP) to improve students' scientific literacy skills - Ika Kartika; Iva Nandya Atika; Friscandany Dhiaz Widyasari; Himawan Putranta (Jurnal Penelitian Pendidikan IPA, 2023)
Indonesia is a cultural nation with a richness of indigenous knowledge that must be conserved, one of which is science education in schools. This study intends to develop an integrated science Subject-Specific Pedagogy (SSP) based on the indigenous knowledge of producing Bobung wooden masks from Gunung Kidul, Yogyakarta, Indonesia and to improve students’ scientific literacy. The study employed the ADDIE-based research methodology, which included needs analysis and preliminary research analysis. Planning and creating rough drafts of the product serve as the design phase, and expert validation and revision serve as the development phase. Implementation in a small number of classes, evaluation through SSP use, and dissemination for grade VIII students. The study's findings were used to create a SSP with components such as a syllabus, lesson plans, student teaching books and modules, student worksheets, and assessment sheets rated as very good based on experts' validation. The produced SSP can raise the scientific literacy of junior high school students in grade VIII with an N-gain of 0.69.